Antioxidant properties of lutein contribute to the protection against lipopolysaccharide-induced uveitis in mice - Yao Xin-Sheng; Yao Nan; Lan Fang; Tsoi Bun; He Rong-Rong; Kurihara Hiroshi (BMC, 2011)
Abstract Background Lutein is an important eye-protective nutrient. This study investigates the protective effects and mechanisms of lutein on lipopolysaccharides (LPS)-induced uveitis in mice. Methods Lutein, suspended in drinking water at a final concentration of 12.5 and 25 mg/mL, was administered to mice at 0.1 mL/10 g body weight for five consecutive days. Control and model group received drinking water only. Uveitis was induced by injecting LPS (100 mg per mouse) into the footpad in the model and lutein groups on day 5 after the last drug administration. Eyes of the mice were collected 24 hours after the LPS injection for the detection of indicators using commercial kits and reverse transcription-polymerase chain reaction. Results LPS-induced uveitis was confirmed by significant pathological damage and increased the nitric oxide level in eye tissue of BALB/C mice 24 hours after the footpad injection. The elevated nitric oxide level was significantly reduced by oral administration of lutein (125 and 500 mg/kg/d for five days) before LPS injection. Moreover, lutein decreased the malondialdehyde content, increased the oxygen radical absorbance capacity level, glutathione, the vitamin C contents and total superoxide dismutase (SOD) and glutathione peroxidase (GPx) activities. Lutein further increased expressions of copper-zinc SOD, manganese SOD and GPx mRNA. Conclusion The antioxidant properties of lutein contribute to the protection against LPS-induced uveitis, partially through the intervention of inflammation process.